Conceptual design of S3FEL cryogenic system. Issue 1 (1st May 2022) - Hu, L B; Wang, X L; Yang, L; Lai, B H; Dong, X B; Cui, G L; Sun, Z
Abstract: A new project called Shenzhen SRF Soft Free Electron Laser (S 3 FEL) is under proposal phase at Institute of Advanced Science Facilities, Shenzhen (IASF), in China. The purpose is to produce high intensity coherent X-ray with laser properties. The S 3 FEL accelerator is based on the TESLA technologies and will deliver electrons with the energies of up to 2.5GeV. The electrons will be accelerated by 1.3 GHz superconducting cavities cooled down to the 2 K level. The 2 K cryostat will be protected against heat radiation and conduction by means of one thermal shields at 40- 80 K level and one thermal intercept at 4.5 – 8 K level. The S3FEL accelerator consists of twenty-six 1.3 GHz and two 3.9 GHz cryomodules, both operated in CW modes. Four independent cryoplants will be used for the S 3 FEL project. A 500 W@2 K helium refrigerator will be used for the test facility including two vertical test benches (VTB) for cavities, one magnet test bench for the superconducting magnet (MTB) and three horizontal test benches (HTBs) for cryomodules. A 1 kW@2 K helium refrigerator will be used for the prototype machine for R&D purpose of the superconducting accelerator. Two cryogenic plants with 4 kW@2 K refrigeration capacity will be used for supporting the S 3 FEL accelerator cryogenic cooling requirement. Ideally, one should have enough capacity to supply the cooling for the whole LINAC and the other is acting as a complete set of back up to keep the high availability. In addition, the second plant could compensate the cavity performance degradation due to the long term running or the unexpected cavity performance during the manufacture process. This paper describes the conceptual design of the S 3 FEL cryogenic system. The performance of the cryogenic system and the project schedule are also described.